2019
DOI: 10.1111/pan.13760
|View full text |Cite
|
Sign up to set email alerts
|

Should nitrous oxide ever be used in oncology patients receiving methotrexate therapy?

Abstract: Nitrous oxide (N2O) is frequently used for short anaesthesia/analgesia in children undergoing painful or repetitive procedures 1. Children with acute lymphoblastic leukaemia (ALL) require repeated lumbar punctures with direct instillation of intrathecal chemotherapy, usually the anti-folate agent Methotrexate, during their treatment. These procedures are frequently performed under anaesthesia. Concerns have been intermittently raised about a drug-interaction between methotrexate and N2O that may potentiate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…However, healthy pediatric patients undergoing spinal interventions for up to 8 h did not develop any evidence of megaloblastic anemia 37 . Obviously, children with cancer are of special concern because of the possible interaction (additive effects) between N 2 O and certain chemotherapeutic agents 38 . Their bone marrow is more fragile (immunosuppression, anemia) and some chemotherapies are neurotoxic (e.g., vincristine).…”
Section: Discussionmentioning
confidence: 99%
“…However, healthy pediatric patients undergoing spinal interventions for up to 8 h did not develop any evidence of megaloblastic anemia 37 . Obviously, children with cancer are of special concern because of the possible interaction (additive effects) between N 2 O and certain chemotherapeutic agents 38 . Their bone marrow is more fragile (immunosuppression, anemia) and some chemotherapies are neurotoxic (e.g., vincristine).…”
Section: Discussionmentioning
confidence: 99%
“…For some children who prefer this, nitrous oxide can be a good alternative with few side effects to general anesthesia for minor procedures. 30 However, due to the risk of interactions, 31 the use of nitrous oxide in lumbar punctures in pediatric oncology is limited since many chemotherapy regimens include intrathecal administration of methotrexate followed by intravenous high-dose methotrexate, which may be potentiated by nitrous oxide. 31 More nurses and physicians reported that children with cancer experience moderate-to-severe pain.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, due to the risk of interactions, 31 the use of nitrous oxide in lumbar punctures in pediatric oncology is limited since many chemotherapy regimens include intrathecal administration of methotrexate followed by intravenous high-dose methotrexate, which may be potentiated by nitrous oxide. 31 More nurses and physicians reported that children with cancer experience moderate-to-severe pain. However, there were fewer nurses and physicians who believed that more effective treatment of pain was possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se debería tener en cuenta los niveles de vitamina B12 en pacientes propensos a tener efectos neurotóxicos por metotrexato 21 . Otros autores como Forster VJ, Bell G, Halsey C. también han hecho referencia a ciertas interacciones entre diversos componentes que pueden inducir riesgo en la salud de los pacientes con leucemia Linfoblástica en tratamiento con metotrexate 22 También Deepa Bhojwani et al señalaron que el metotrexato (MTX) puede causar neurotoxicidad clínica significativa y leucoencefalopatía asintomática. Buscamos identificar factores de riesgo clínicos, farmacocinéticas y genéticos para estas toxicidades relacionadas con el MTX durante la terapia de leucemia linfoblástica aguda (LLA) infantil y proporcionar datos sobre la seguridad de la reexposición intratecal y de dosis altas de MTX en pacientes con neurotoxicidad.…”
Section: Introducción Y Justificacionunclassified